Impact of AI-ChatGPT Intervention on Coding: NPL Supportive Approach to Teaching and Learning Effectiveness - Muraina, Ismail Olaniyi; Adesanya, Muyideen Olayemi (Journal of Educational Sciences, 2024)
AI-ChatGPT is increasingly popular among all individuals, particularly researchers, educators, and students. This fantastic tool was created to generate human-like text in response to user inputs, making it ideal for chatbots and other conversational systems. Because of its capacity to solve various problems such as choice difficulties, prediction problems, and coding problems, it may be readily linked with programming learning to increase and interest students in coding challenges that typically encountered during traditional programming language learning. This study combines a programming language for teaching and learning, such as Python, with ChatGPT to determine whether it will be a valuable tool for students' programming expertise. The assignment was carried out using a basic randomised controlled approach to ensure that no students from either group had previous information about what to accomplish before being assigned to the groups; also, the gender of the students was balanced. Results showed that the experimental group performed better in the Pre-Test and Post-Test after exposure to diverse teaching methods. The study emphasises the importance of ChatGPT implementation in Python programming and the importance of a randomised controlled approach.